Analysis of Customer Relationship Management Effects Toward Lovaltv of Consumers at Kafe XYZ - Lily Suhaily; Anggini Ekatumiri Septisesari (Business and Entrepreneurial Review, 2006)
Effect of Customer Relationship Marketing program at Kafe XYZ Menteng toward loyalty of consumer is the aim of this research. Data are collected by spreading 100 questionnaires to visitors at Kafe XYZ. Menteng using convenience sapling method. The spread of questionnaires was done from 2 October 2006 up to 16 October 2006. Research finding indicates that there has been effect of Customer Relationship Marketing program taken at Kafe XYZ toward loyalty of consumer.